DFIG use with combined strategy in case of failure of wind farm - Azeddine Loulijat; Najib Ababssi; Mohammed Makhad (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In the wind power area, Doubly Fed Induction Generator (DFIG) has many advantages due to its ability to provide power to voltage and constant frequency during rotor speed changes, which provides better wind capture as compared to fixed speed wind turbines (WTs). The high sensitivity of the DFIG towards electrical faults brings up many challenges in terms of compliance with requirements imposed by the operators of electrical networks. Indeed, in case of a fault in the network, wind power stations are switched off automatically to avoid damage in wind turbines, but now the network connection requirements impose stricter regulations on wind farms in particular in terms of Low Voltage Ride through (LVRT), and network support capabilities. In order to comply with these codes, it is crucial for wind turbines to redesign advanced control, for which wind turbines must, when detecting an abnormal voltage, stay connected to provide reactive power ensuring a safe and reliable operation of the network during and after the fault. The objective of this work is to offer solutions that enable wind turbines remain connected generators, after such a significant voltage drop. We managed to make an improvement of classical control, whose effectiveness has been verified for low voltage dips. For voltage descents, we proposed protection devices as the Stator Damping Resistance (SDR) and the CROWBAR. Finally, we developed a strategy of combining the solutions, and depending on the depth of the sag, the choice of the optimal solution is performed.